2021
DOI: 10.1101/2021.10.21.465257
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of two cancer stem cell-like populations in triple-negative breast cancer xenografts

Abstract: Gene expression analysis at the single-cell scale by next generation sequencing has revealed the existence of clonal dissemination in cancer metastasis. The current spatial analysis technologies elucidate the heterogeneity of cell-cell interactions in situ; however, further analysis is needed to elucidate the nature of tumor heterogeneity. To reveal the expressional heterogeneity and cell-cell interactions in primary tumors and metastases, we performed transcriptomic analysis of microtissues dissected from a t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 78 publications
(137 reference statements)
0
4
0
Order By: Relevance
“…[22,23] Silencing HMGA1 can block the metastasis of breast cancer and colorectal cancer and reduce the proportion of tumor stem cells. [24–26] As reported in a recent study, the high expression of HMGA1 may be induced by the secretion of breast cancer cells, and signals may be sent through the advanced glycation end-products receptor, which would promote invasiveness. [26] In addition, previous studies demonstrated that the overexpression of HMGA1 can regulate the epigenetic silencing of genes related to tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…[22,23] Silencing HMGA1 can block the metastasis of breast cancer and colorectal cancer and reduce the proportion of tumor stem cells. [24–26] As reported in a recent study, the high expression of HMGA1 may be induced by the secretion of breast cancer cells, and signals may be sent through the advanced glycation end-products receptor, which would promote invasiveness. [26] In addition, previous studies demonstrated that the overexpression of HMGA1 can regulate the epigenetic silencing of genes related to tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Figures 10C and 10D display representative images of metastatic tumors in the liver. The MDA-MB-231 tumor used in the xenograft model is well-known to metastasize to various organs, including the liver, lymph nodes, lungs, bones, and brain [ 36 ]. Although the nanoparticle formulation inhibited cell migration in vitro , a similar effect was not observed in vivo at the current dose.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 1.0×10 6 NMuMG-luc-HOXB7 cells, NMuMG-luc-HOXB7-shGFP cells, or NMuMG-luc-HOXB7-shSTAT3#3 cells were transplanted into fourth fat pads of 6-weeks-old BALB/cSlc-nu/nu female mice as previously described (Nakayama et al . 2017; Nakayama et al . 2022).…”
Section: Methodsmentioning
confidence: 99%